Le contraddizioni della generazione e le pratiche simboliche delle donne. La Condizione fetale di Luc Boltanski: una sfida per la sociologia pragmatica - Ferrando, Stefania (SocietàMutamentoPolitica, 2021)
The paper argues that the sociological analysis of generation and abortion presented in The Foetal Condition constitutes a radicalisation of the sociology of critique and a challenge to it with respect to the understanding of authority and power. The challenge this book faces is to conceive of a freedom that is not liberal, not absolutized or individualistic. This freedom emerges as an issue in the words of the women interviewed in the research underlying The Foetal Condition. We will try to identify the reason the book’s analyses cannot fully understand it, identifying the main problem in the articulation of the notions of authority and power.